Site wiki in the classroom: a experience with hypertextuality - Gomes, Mayra Rodrigues (Comunicação & Educação, 2009)
This paper is about the adoption of the wiki resource, in courses dedicate to language theories, aiming to encourage research and to present diversified resources to the students, with the workin hypertext ambiance. After two years of application, we present the observations about text production in wiki sites installedfor under-graduated students of journalism.